2016
DOI: 10.1080/14616696.2016.1235218
|View full text |Cite
|
Sign up to set email alerts
|

European parents’ attitudes towards public childcare provision: the role of current provisions, interests and ideologies

Abstract: Despite the large volume of literature on childcare provision across countries, individuals' attitudes and preferences concerning the role of government in the provision of childcare remain largely unexplored. This study examines how current policy provision structures, measured through objective and subjective indicators, both at the individual and national levels, influence the degree to which parents in European countries support public provision of childcare. The relative importance of current provision st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 39 publications
(47 reference statements)
3
56
0
2
Order By: Relevance
“…Rather than completely abandoning public education when dissatisfied with the current performance, respondents favour more public investments in those educational sectors which are perceived to contribute to the solution of pressing socio-economic problems. Following Chung and Meuleman (2017), this can be called an 'improvement reaction' rather than a 'punishment reaction' from critical citizens (p. 51).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than completely abandoning public education when dissatisfied with the current performance, respondents favour more public investments in those educational sectors which are perceived to contribute to the solution of pressing socio-economic problems. Following Chung and Meuleman (2017), this can be called an 'improvement reaction' rather than a 'punishment reaction' from critical citizens (p. 51).…”
Section: Discussionmentioning
confidence: 99%
“…The partnership status of the respondent (married or partnered vs. non-partnered) is also included as a control variable for it reflects the presence of alternate caregivers in the household. Nonetheless, except for the decision to use childcare before the child reaches 18 months of age (Zachrisson et al 2013), this variable is found to have a significant effect on neither the type or intensity of childcare use (Geoffroy et al 2012;Sylva et al 2007;Tang et al 2012), nor the attitudes towards public childcare provision (Chung and Meuleman 2017).…”
Section: Micro-level Control Variablesmentioning
confidence: 80%
“…This model suggests that we take into account various dimensions such as the child, the mother (and sometimes the father), the family and environmental characteristics, as well as maternal well-being and cultural beliefs and preferences with regard to childcare when identifying the determinants of the type and intensity of ECEC used. A similar list of variables is also used in a recent study on attitudes towards public childcare (Chung and Meuleman 2017). This framework also meets our needs in controlling for the individual-, household-or family-related factors that may affect the perception of childcare accessibility.…”
Section: Micro-level Control Variablesmentioning
confidence: 99%
“…Оно диктуется, в первую очередь, (1) собственными интересами населения [Blekesaune, Quadagno, 2003;Knijn, van Oorschot, 2008] и (2) идеологическими паттернами [Blekesaune, 2013;Edlund, 2006;Hasenfeld, RaVerty, 1989;Groskind, 1994, Jaeger, 2006, которые в зависимости от позиций исследователей также могут дополняться спецификой социализации, паттернами национальной культуры в отношении социальной поли тики, текущей конфигурацией социальной сферы и т. д. [Blekesaune, 2013;Chung, Meuleman, 2017;Chung et al, 2018;Kootstra, Roosma, 2018 и др.]. Значимость индивидуальных интересов в вопросе восприятия политики все общего благосостояния и отдельных ее механизмов многократно подтверж дена эмпирическими исследованиями.…”
Section: запрос населения к социальной политике: теоретический анализunclassified